LOOKING AT VIETNAMESE TEACHERS' JAPANESE PROFICIENCY FROM THE ANGLE OF THE LINKS BETWEEN THE EXPERIENCE OF LEARNING THE LANGUAGE AT THE BEGINNING STAGE AND THE TEACHERS' BELIEF (Journal of Foreign Language Studies, 2008)
.